Lifestyle and Problems of HIV Sufferers in Surabaya: Phenomenological Study - Taufan Citra Darmawan; Lina Mahayaty; Retty Nirmala (Nursing and Health Sciences Journal (NHSJ), 2023)
People living with HIV AIDS (PLWHA) are someone who experiences physical, and psychosocial life threats, and social problems such as anxiety and depression. PLWHA are also very vulnerable to stigma which results in community discrimination. The complexity of the problems experienced by PLWHA requires special attention to be resolved immediately. The purpose of this research was to explore the lifestyle and problems of people living with HIV AIDS (PLWHA). This research uses a phenomenological study. The ethical test was obtained from STIKes William Booth. There are 5 informants selected based on the purposive sampling technique. The data was taken by means of an open-question questionnaire. Each respondent was given questions using the interview method and then recorded. There were 2 main topics that were asked, the first topic is the initial condition of being diagnosed with HIV and the secondary topic is the lifestyle and current problems. The results of the interviews found that the sample had suffered from HIV 5-8 years ago due to risky behavior. Diagnosed because he felt the symptoms of a disease that did not cure. Psychosocial complaints stem from internal feelings such as feelings of guilt, having no future, and fear of death. In addition, the problem of external stigma greatly threatens social relations activities with other people. Continuous social support is a basic need. Spending time alone and working became daily activities. HIV community groups are difficult to reach because of distance. Activities do not vary due to physical constraints such as the effects of medication and co-morbidities. Some have tried to exercise but are less successful. Need the right way to reduce the physical constraints felt by PLWHA, psychosocial support is needed to change the mindset of PLWHA. Sustainable programs that can reduce community stigmatization are the key to changing the quality of life of PLWHA.